Estimates of the global workforce required for providing assistive technology: a modeling study - Johanna Rosberg Petersson; Malin Tistad; Malin Tistad; Sébastien Muller; Irene Calvo; Johan Borg (Frontiers in Rehabilitation Sciences, 2025)
IntroductionDespite being a fundamental human right, access to assistive products varies between 3% and 90% across countries. Ensuring adequate and trained human resources is a prerequisite for improving access to assistive products. To support workforce planning and development, this study estimated the global workforce required for assistive technology provision to achieve a high level of access.MethodThis modeling study used estimates of the primary workforce for assistive technology provision and assistive product needs in a country with a high level of access and global assistive product needs, to predict the global workforce required to provide assistive technology in five product domains: cognition and communication, hearing, mobility and self-care, orthotics and prosthetics, and vision. The assistive product need estimates were based on self-reported data from WHO Rapid Assistive Technology Assessment surveys in 28 countries.ResultsA total workforce for assistive technology provision of 4.4 (95% CI: 3.0–6.8) million full-time equivalents (FTE) would be required globally to achieve a high level of access to assistive products. Excluding the administrative workforce, this includes a workforce of 3.4 (2.3–5.4) million FTE, composed of 1.7 (1.3–2.2) million FTE providing mobility and self-care products, 0.9 (0.5–1.7) million FTE providing orthoses and prostheses, 0.5 (0.2–1.0) million FTE providing vision products, 0.3 (0.2–0.4) million FTE providing hearing products, and 0.05 (0.04–0.06) million FTE providing cognition and communication products.ConclusionLikely a conservative estimate of the required workforce size, this provides a cautious foundation for informing strategies to develop a workforce capable of meeting global assistive product needs and improving access.